Towards an age-friendly city: The constraints preventing the elderly's participation in community programs in Akita City - Yoshihiko Kadoya (Osaka University, Institute of Social and Economic Research (ISER), 2013)
The inclusion of the elderly in community life is a major factor in achieving an age-friendly city. However, there has been little research investigating the constraints preventing the elderly's interaction with society. With that in mind, this paper is pioneering the investigation of such constraints using the results from the Questionnaire towards an Age-Friendly City by Akita City Government in Japan, a member of the World Health Organization (WHO)'s Global Network of Age-friendly Cities and Communities. This paper reveals two policy implications. First, living with someone encourages elderly to interact with society. Second, the elderly's ability to be mobile fosters their social participation.
Keywords: 330; age-friendly city; aging; elderly's social participation; community programs; isolation; Alternde Bevölkerung; Alte Menschen; Soziale Integration; Partizipation; Soziale Isolation; Japan